Epoxy resin/phosphorus‐based microcapsules: Their synergistic effect on flame retardation properties of high‐density polyethylene/graphene nanoplatelets composites. Issue 34 (25th May 2018) - Xia, Yanping; Tang, Rui; Tao, Shengxi; Tao, Guoliang; Gong, Fanghong; Liu, Chunlin; Cao, Zheng
ABSTRACT: Two types of microcapsule flame retardants are prepared by coating ammonium polyphosphate (APP) and aluminum diethylphosphinate (ADP) with epoxy resin (EP) as the shell via in situ polymerization, and blended with high density polyethylene (HDPE)/graphene nanoplatelets (GNPs) composites to obtain flame‐retardant HDPE materials. Fourier transform infrared spectroscopy, scanning electron microscopy (SEM), and water contact angle results confirm the formation of core–shell structures of EP@APP and EP@ADP. The limiting oxygen index (LOI), vertical burning test (UL‐94), cone calorimetry, and Raman spectroscopy are employed to characterize the HDPE/GNPs composites filled with EP@APP and EP@ADP core–shell materials. A UL94 V‐0 level and LOI of 34% is achieved, and the two flame retardants incorporated in the HDPE/GNPs composite at 20 wt % in total play a synergistic effect in the flame retardancy of the composite at a mass ratio of EP@ADP:EP@APP = 2:1. According to the cone‐calorimetric data, the compounding composites present much lower peak heat release rate (300 kW/m 2 ) and total heat release (99.4 MJ/m 2 ) than those of pure HDPE. Raman spectroscopic analysis of the composites after combustion reveals that the degree of graphitization of the residual char can reach 2.31, indicating the remarkable flame retarding property of the composites. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46662. Abstract :